Interactive synthesis and visualisation of vast areas with geometrically diverse trees - Kohek, Štefan (Informatica, 2020)
This paper summarises a Doctoral Thesis which proposes a new approach for large- scale forest visualisation with geometrically diverse trees. The main contribution of the proposed method is an interactive visualisation of numerous trees without generating geometric data in advance, which is achieved by a new method for on-the-fly tree skeleton synthesis with a specific level of detail, and by a new procedural volumetric tree crown visualisation which avoids geometry formation altogether. The proposed method enables visualisation of forests with millions of trees, thus allowing rendering more trees than geometry-based visualisation methods.